Flouting Maxims by Indonesia Presidential Candidates in Najwa Shihab’s Talk Show - Vivin Agustin; Sri Minda Murni; Fauziah Khairani Lubis (RIRAI Publisher, 2024)
This study investigates the flouting of conversational maxims by Prabowo Subianto and Gibran Rakabuming Raka in the